Optimizing granular activated carbon (coal and peat-base) for malathion removal from agricultural effluent - Jusoh, Hajjar Hartini Wan; Juahir, Hafizan; Ismail, Azimah; Mohd Nasir, Nurfarahana (ResearchersLinks, 2024)
The usage of malathion pesticide and a subsequent release into the environment was a major concern worldwide due to detrimental effect and their toxicity to ecosystem. Concerned about the impact of malathion pesticide, this study investigated the effectiveness of granular activated carbon (GAC) in removing malathion from agricultural runoff. The study focused on how particle size and dosage of GAC impact the removal efficiency. Therefore, this study revealed that particle size and dosage of granular activated carbon significantly affect the removal efficiency of malathion from agricultural runoff. As the initial malathion concentration (7 μg L-1) was lowered to approximately 1.14 and 1.5 μg L-1 for CBAC and 2.87 μg L-1 for PBAC at respective diameters of 0.063 and 1.0 mm, the best circumstances for the highest removal efficiency of 90 % were observed.The features of adsorption behavior were described using the Langmuir and Freundlich adsorption isotherms models. The Freundlich and Langmuir models, with a maximum adsorption capacity of 248.1 mg g-1, suit the equilibrium results quite well. Therefore, this study highlights the potential of GAC as an effective absorbent material for the removal of malathion from agricultural runoff, with significant implications for mitigating the damaging consequences of environmental pesticide pollution.